Feeding and nutrition in children with neurodevelopmental disability - Sullivan, Peter B. (Practical Guide from Mac Keith Press., 2009)
For those responsible for the nutritional and gastrointestinal care of children with neurodisability, including cerebral palsy. Covering the problems surrounding the nutritional management of children with neurological impairment who have difficulty swallowing and feeding. Written from a multidisciplinary perspective.